miR-145-5p Inhibits Neuroendocrine Differentiation and Tumor Growth by Regulating the SOX11/MYCN Axis in Prostate cancer - Ji, Shuya; Shi, Yi; Yang, Lin; Zhang, Feng; Li, Yong; Xu, Feng (Frontiers in Genetics, 2022)
Recent studies have shown that the downregulation of miR-145-5p in prostate cancer (PCa) is significantly associated with poor differentiation and prognosis. We aimed to investigate the biological role of miR-145-5p in the neuroendocrine differentiation (NED) of PCa. In this study, The Cancer Genome Atlas was used to identify the association of miR-145-5p with PCa. The functions of miR-145-5p were evaluated using the Cell Counting Kit-8 (CCK-8) assay and cell cycle analysis. We validated changes in cell cycle control by testing the expression of cyclin-related genes by western blot. The luciferase reporter assay was performed to test miR-145-5p-targeting genes and direct transcriptional targets of SOX11. The expression of miR-145-5p was found to be significantly downregulated in castration-resistant PCa, and this was correlated with higher Gleason score and prostate-specific antigen. We confirmed these results using PC3 and LNCaP cell lines depicted a gradual decline of miR-145-5p while the cells were cultured under androgen depletion conditions. Moreover, the knockdown of miR-145-5p significantly promoted NED and proliferation of LNCaP cells, whereas overexpression of miR-145-5p significantly inhibited NED and proliferation of LNCaP cells. Mechanistically, we found that SOX11 was a direct target of miR-145-5p, which regulates MYCN might mediate induction of NED and proliferation of LNCaP cells. Furthermore, knockdown of miR-145-5p promoted tumor growth in vivo. Our findings suggest that miR-145-5p can inhibit NED and tumor growth by targeting SOX11, which regulates the expression of MYCN, and that this could be a novel therapeutic strategy for preventing the progression of PCa.